Influence of facilities of physical rehabilitation on the state of the cardiovascular system of sportsmen at the initial degrees of the overtraining syndrome - Пєшкова [Olga Peshkova] Ольга Володимрівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 12.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; text-transform: uppercase; mso-ansi-language: EN-GB; mso-fareast-language: RU; mso-bidi-language: AR-SA;" lang="EN-GB">is considering the dynamics of reaction of the cardiovascular system of sportsmen on tests with the additional standard physical loading at the initial degrees of <span style="font-size: 12.0pt; mso-bidi-font-size: 14.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; color: black; mso-ansi-language: EN-GB; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">the overtraining syndrome. The types of reactions of the cardiovascular system are described on these loading at the inspected contingent of sportsmen. The speeds <span style="font-size: 12.0pt; mso-bidi-font-size: 14.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman CYR’; color: black; mso-ansi-language: EN-GB; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">data of <span style="font-size: 12.0pt; mso-bidi-font-size: 14.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman CYR’; color: black; mso-ansi-language: EN-GB; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">reduction processes given about a dynamics are brought after the dosed physical loading on the sizes of index of Harvard <span style="font-size: 12.0pt; mso-bidi-font-size: 14.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman CYR’; color: black; mso-ansi-language: EN-GB; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-GB">step-test.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>